Pengaruh Kompetensi Pegawai Motivasi Kerja dan Disiplin Kerja Terhadap Kinerja Pegawai Melalui Kepuasan Kerja Sebagai Variabel Intervening Pada Kantor Badan Meteorologi Klimatologi dan Geofisika (Bmkg) Stasiun Meteorologi Mali – Kabupaten Alor - Peny, Theresia Lounggina Luisa; Bainhana, Isak; Esehana, Yeheskia Laazar (Peneliti.net, 2024)
This study aims to determine the Influence of Employee Competence, Work Motivation and Work Discipline on Employee Performance Through Job Satisfaction as an Intervening Variable at the Meteorology, Climatology and Geophysics Agency (BMKG) Mali Meteorological Station - Alor Regency, both partial or simultaneous influences and also direct or indirect influences on employee performance. The respondents of this study were 17 employees. Data collection used questionnaire techniques, observation, and documentation studies. The data were then analyzed using the t-test to determine the partial influence and the F-test to determine the simultaneous influence on performance. From the results of the research and the conclusions of the research, the research team suggests that Respondents (employees of the Meteorology, Climatology and Geophysics Agency, Mali Meteorological Station, Alor Regency) are expected to maintain employee performance that has been well organized until now, while continuing to improve themselves considering various changes in work situations. Suggestions are also given to the Head of the Meteorology, Climatology and Geophysics Agency, Mali Meteorological Station, Alor Regency, so that leaders who have protected and built employee competency values, work motivation, work discipline and job satisfaction that have been well embedded in this work scope can be maintained and by continuing to provide enthusiasm, motivation and innovation for the development of much better employee performance and the performance of the Meteorology, Climatology and Geophysics Agency, Mali Meteorological Station, Alor Regency as an institution.